3D bioprinted glioma microenvironment for glioma vascularization. Issue 6 (25th August 2020) - Wang, Xuanzhi; Li, Xinda; Ding, Jinju; Long, Xiaoyan; Zhang, Haitao; Zhang, Xinzhi; Jiang, Xiaochun; Xu, Tao
Abstract: Glioblastoma is the most frequently diagnosed primary malignant brain tumor with unfavourable prognosis and high mortality. One of its key features is the extensive abnormal vascular network. Up to now, the mechanism of angiogenesis and the origin of tumor vascularization remain controversial. It is essential to establish an ideal preclinical tumor model to elucidate the mechanism of tumor vascularization, and the role of tumor cells in this process. In this study, both U118 cell and GSC23 cell exhibited good printability and cell proliferation. Compared with 3D‐U118, 3D‐GSC23 had a greater ability to form cell spheroids, to secrete vascular endothelial growth factor (VEGFA), and to form tubule‐like structures in vitro. More importantly, 3D‐glioma stem cells (GSC)23 cells had a greater power to transdifferentiate into functional endothelial cells, and blood vessels composed of tumor cells with an abnormal endothelial phenotype was observed in vivo. In summary, 3D bioprinted hydrogel scaffold provided a suitable tumor microenvironment (TME) for glioma cells and GSCs. This bioprinted model supported a novel TME for the research of glioma cells, especially GSCs in glioma vascularization and therapeutic targeting of tumor angiogenesis.